KARAKTERISTIK MINYAK ATSIRI BUNGA KAMBOJA CENDANA (Plumeria alba) PADA PERLAKUAN LAMA PROSES DISTILASI - Agung Paranatha, I Gusti Ngurah; Wartini, Ni Made; Gunam, Ida Bagus Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 1 No 1 (2013): September, 2013)
The aims of this study were to determine characteristic of sandalwood frangipani essential oil that come from the distilation process. This research used randomized block design, six levels with the distillation process time namely: 1, 2, 3, 4, 5, and 6 hours. Observed variables were the rendement, like of fragrance and the levels of fragrance strenght of sandalwood frangipani essential oil The result showed that the distilatian process timehad significant effect on the rendement and the characteristic of sandalwood frangipani essential oil that has been produced. The distillation process time offive hours was the best treatment to produced sandalwood frangipani essential oil with 0,0047% sandalwood frangipani essential oil rendement, 4.75like of fragrance (from netral to kinda like) and 2,16 (the most powerful) lihat kesimpulan...
Keywords: 9